Role of antibiotic prophylaxis on surgical site infection prevention in a low-risk population undergoing laparoscopic cholecystectomy: A randomized controlled study. (June 2022) - Ullah, Kaleem; Dogar, Abdul Wahab; Jan, ZakaUllah; Bilal, Hafiz; Tahir, Muhammad Junaid; Hamza, Ameer; Asghar, Muhammad Sohaib; Yousuf, Zohaib
Abstract: Objective: To compare the incidence of surgical site infections (SSIs) in low-risk patients undergoing laparoscopic cholecystectomy (LC) with pre-operative antibiotics versus no pre-operative antibiotics administration. Study design: Randomized controlled study. Setting: Hepatobiliary department, Pir Abdul Qadir Shah Jeelani Institute of Medical Sciences, Pakistan, from Jul 1, 2018, to Jun 30, 2021. Methods: This is a prospective, open-label, randomized study. Individuals scheduled for laparoscopic cholecystectomy who met the inclusion requirements were randomly assigned to two groups. Group A patients received pre-operative antibiotics (intravenous cefazolin 2-g), and group B patients were operated on without administration of pre-operative antibiotics. Post-operatively, patients were studied for the occurrence of SSIs for 30 days. Results: The mean age of patients in group A was 40.6 + 5.2 years, while group B was 41.04 + 5.03. The male to female ratio was 1:3. Gender distribution showed female dominance in both groups, i.e., 78.74% in group A and 76.80% in group B. The incidence of SSI in group A was 3.98%, while in group B was 4.9% (p-value = 0.584). No statistical significance was found while comparing both groups' age, gender, operative duration, and hospital stay. Conclusion: This study showed comparable results between both groups, and prophylactic antibiotics have no impact in preventing SSIs. In low-risk individuals undergoing laparoscopic cholecystectomy, the incidence of SSIs is quite low, and prophylactic antibiotics can be avoided. Highlights: One of the postoperative complications following cholecystectomy is surgical site infections (SSIs). This study aimed to determine the effectiveness of preoperative antibiotic prophylaxis in preventing SSIs. We found that prophylactic antibiotics have no impact in preventing SSIs in low-risk individuals undergoing laparoscopic cholecystectomy.